UPAYA MEMBINA HUBUNGAN SOSIAL MELALUI BIMBINGAN KELOMPOK DI SMK NEGERI 2 PULAU PUNJUNG KABUPATEN DHARMASRAYA - Ramayani, Ika; Kasih, Fitria; Gusneli, Gusneli (Bimbingan dan Konseling, 2013)
Social relationship is a relationship between people who need each other. Phenomena that occur in students related to social relationships is having problems students misunderstandings when it comes, it often happens that is not related to the social good. Group counseling services are in guidance and counseling services that can be used to improve the learners social relationships. By conducting group counseling services, students will be given the understanding and practice. This study aims to reveal the effectiveness of group counseling services in improving learners social relationships. This study aims to reveal the effectiveness of group counseling services in improving learners social relationships. This type of research is experimental with pretest and posttest design was used to test whether group counseling services can improve learners social relationships . Two groups are selected using purposive sampling is in class X SMK N 2 Island Arbor . Each group consisted of 11 students. Group counseling services with the application of the experimental group while the control group did not apply group counseling services . Collected data on social relationships statistical method of Pearson Product Moment using excel program. The findings of this study are: There are significant differences between the social relationships that learners control group was not given guidance services group with social relationships learners experimental group given group counseling services.